Pengaruh Financial Distress, Tingkat Hutang, Growth Opportunity, Political Cost Terhadap Konservatisme Akuntansi (Studi Empiris Pada Perusahaan Manfaktur Barang Konsumsi Yang Terdaftar Di Bei Tahun 2016-2020) - Mohamad Ramlan; Lely Suryani (Publikasi Inspirasi Indonesia, 2025)
Abstract This study aims to examine the effect of Financial distress, Debt Level, Growth opportunity, and Political Cost. The independent variable used in this study is Accounting Conservatism. While the dependent variable in this study is Financial distress, Debt Level, Growth opportunity, and Political Cost, and in this study is Accounting Conservatism. The type of research used is quantitative research. Sources of data used in this study is secondary data. The population in this study is an empirical study on manufacturing companies listed on the IDX in 2016-2020. Determination of the sample in this study using the purposive sampling method and obtained as many as 51 companies in a period of 5 years so that the sample in this study was 21. The analytical method used was multiple linear regression analysis using E-Views version 9 software.The results of this study indicate that financial distress has no effect on accounting conservatism. The level of debt has a significant effect on accounting conservatism. Growth opportunity has no significant effect on accounting conservatism. Political cost has a significant effect on accounting conservatism.